IMPLEMENTASI PROGRAM PENCATATAN AKTA KELAHIRAN BERBASIS ONLINE (STUDI KASUS PROGRAM INOVASI CAPIL ONLINE PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA DENPASAR) - Widhiastiti, Ni Made Setiawati; Dewi Pascarani, Ni Nyoman; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2017)
ABSTRACT Administrative service population requires public participation to participate and involved in it to create population administration, one of which can be realized through the ownership of a birth certificate. Through innovation program capil online, Denpasar city government seeks to create a birth certificate recording process more efficient by involving hospitals and clinics that serve labor. The problems of the background for this study is the uneffective implementation of the innovation program capil online as evidenced by the lack of socialization, uneven program availability, requirements that are not efficient, often damage electronic equipment and the low number of users. This research was conducted using descriptive qualitative data collection techniques such as in-depth interviews by using several informants. This study measured how the implementation of program-based registration of birth certificates online through innovation program capil online in the department of population and civil registration Denpasar with the theory of public policy implementation (George.C.Edward III), which consist of an indicator of communication, resources, disposition and bureaucratic structure. The result of this study indicate that online capil innovation programs implementation at the department of population and civil registration Denpasar is still not effective due to its implementation, which already cannot be done online due to the damaged program and the absence of overall responsibility from relevant agencies. Based on the four indicators used, only the disposition indicators that show good results whereas other indicators such as communication, resources and bureaucratic structures are still less than the maximum. Keywords : Implementation, Innovation Program, Online Birth Certificates